Structure and correlation in the detection of melodic sequences - Lee, J.; Leung, F.; Satkunasingham, J.; Wong, W.; Wong, W. (Canadian Acoustics, 2001)
The detection performance of randomly generated signals of varying degrees of structural content was measured. Fractal melodies were used and the degree of self-correlation (structural content) was changed in a continuous manner. Overall, significant results were obtained.